Global Initiatives in Environmental Security: The Need for Policy Revisions: Addressing the Challenges of Environmental Security in the Globalized World (Journal of Advances and Scholarly Researches in Allied Education, 2017)
After the collapse of the Soviet Union, the unequal transition trends in economic, political, and technological forces occurred, often labelled globalisation.One of the repercussions of this has been the introduction of a new concept human security. Nations of the world started to think about the integrity of the government and the community. Though we liberated ourselves from the danger of major-power war, environmental destruction and natural disasters pose a major threat to human life. The United Nations Security Council has made declarations and resolutions on the tie between natural and manmade disasters and resources and the incorporation of ecological information into security policy.Security and uncertainty are not restricted to armed war or its exclusion but are embedded in sustainable livelihoods, social care and well-being.This paper analyses the challenge faced by the government and the policies and programmes that can handle the “freedom from hazard impact” principle. By incorporating economic, social, and security processes into security policies and strategy and making intervention to change the asset protection strategies that are currently in effect, as well as focus on developing new sustainability policies.